Breeding goals and economic values for Nellore cattle in a full-cycle production system (Acta Scientiarum. Animal Sciences, 2019)
The objective of this study was to develop a bio-economic model for the estimation of economic values of economically important traits in a full-cycle beef cattle production system. The bio-economic model calculated economic values by simulating the impact of changes in the profit of the system consisting of a 1% increase in each trait of the breeding objective, while the other traits were kept constant. The bio-economic model was effective in estimating the sources of revenues and expenses of the production system. The estimated economic values were, in the order of importance for the full-cycle system, R$ 3.69 for male slaughter weight, R$ 3.63 for male weaning weight, R$ 3.58 for weaning rate, R$ 3.40 for female slaughter weight, R$ 2.30 for female weaning weight, and R$ 0.13 for mature cow weight. The results showed that all traits evaluated in the full-cycle system had positive economic impact, indicating that selection would increase profitability maximizing the expected response for the traits of the breeding goal.